Management of walled-off necrosis with nasocystic irrigation with hydrogen peroxide versus biflanged metal stent: randomized controlled trial - Maharshi, Sudhir; Sharma, Shyam Sunder; Ratra, Sandeep; Sapra, Bharat; Sharma, Dhruv (Endoscopy International Open, 2021)
Background and study aims Walled-off necrosis (WON) is a known complication of acute necrotizing pancreatitis (ANP). There is no study comparing nasocystic irrigation with hydrogen peroxide (H2O2) versus biflanged metal stent (BMS) in the management of WON. The aim of this study was to compare the clinical efficacy of both the treatment strategies.Patients and methods This study was conducted on patients with symptomatic WON who were randomized to nasocystic irrigation with H2O2 (Group A) and BMS placement (Group B). Primary outcomes were clinical and technical success while secondary outcomes were procedure time, adverse events, need for additional procedures, duration of hospitalization, and mortality. Results Fifty patients were randomized into two groups. Group A (n = 25, age 37.8 ± 17.6 years, 16 men) and Group B (n = 25, age 41.8 ± 15.2 years, 17 men). There were no significant differences in baseline characteristics between the two groups. The most common etiology of pancreatitis was alcohol, observed in 27 (54 %) patients. Technical success (100 % vs 96 %, P = 0.98), clinical success (84 % vs 76 %, P = 0.76), requirement of additional procedures (16 % vs 24 %, P = 0.70) and adverse events (4 vs 7, P = 0.06) were comparable in both the groups. The duration to clinical success (34.4 ± 12 vs 14.8 ± 10.8 days, P = 0.001) and procedure time (36 ± 15 vs 18 ± 12 minutes, P = 0.01) were longer in Group A compared to Group B. Conclusions Nasocystic irrigation with H2O2 and BMS are equally effective in the management of WON but time to clinical success and procedure time is longer with nasocystic irrigation.